The way we argue now : a study in the cultures of theory - Anderson, Amanda, 1960- (Princeton University Press, 2006)
In this book, Amanda Anderson examines influential academic debates across the fields of literary, cultural, and political theory. The book combines a pointed critique of the philosophical and political limitations of these theories with an appreciative assessment of the productive internal contests and creative developments.